2019
DOI: 10.1016/j.biortech.2018.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Sewage biogas efficient purification by means of lignocellulosic waste-based activated carbons

Abstract: The present paper evaluates the efficiency of sustainable activated carbons obtained from the valorization of lignocellulosic waste in removing siloxanes and volatile organic compounds for the purification of anaerobic digester biogas. Pyrolized and non-pyrolized lignocellulosic residues generated in food and wood industries were used as precursor materials to obtain experimental adsorbents by a chemical activation process using several activating agents. The highest porosity was obtained by non-pyrolized resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 47 publications
2
20
0
2
Order By: Relevance
“…400 °C), [36,39] which explains the lower pore development achieved with K 2 CO 3 compared to KOH (Table 1). [40–44] Besides, as mentioned above, K 2 CO 3 is one of the products during KOH activation, so that for T >600–700 °C, reactions (1) to (4) also take place during KOH activation, yielding additional pore development. However, K 2 CO 3 has two important additional advantages over KOH.…”
Section: Harmless Chemical Activating Agentsmentioning
confidence: 96%
“…400 °C), [36,39] which explains the lower pore development achieved with K 2 CO 3 compared to KOH (Table 1). [40–44] Besides, as mentioned above, K 2 CO 3 is one of the products during KOH activation, so that for T >600–700 °C, reactions (1) to (4) also take place during KOH activation, yielding additional pore development. However, K 2 CO 3 has two important additional advantages over KOH.…”
Section: Harmless Chemical Activating Agentsmentioning
confidence: 96%
“…However, previous experiences of difficulties in reactor handling, lack of policy framework and technical support in this field are a major bottleneck identified in this paper. It is suggested that biogas plant designers/engineers should always be mindful of leakages, solid retention time, and pressure management for sustainable [92,93] Hydrogen recovery Extracting H 2 gas as energy source [94] Pressure transducer Methane pressure monitoring [95] pH Self-regulation ternary buffer system Process stability [96] VFA control Process stability [97] ORP monitoring and control system…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption onto activated carbon is one of the technologies with the highest overall removal efficiency, although it has a limited efficiency for small siloxane molecules, such as hexamethyldisiloxane [49]. However, the frequently required replacement of the exhausted adsorbent beds [24] increase the operational costs associated, obtaining a score of just 5 in OPEX criterion. Inorganic adsorbents [45,50] are not only more expensive than activated carbon, but also the lifespan of the adsorbent bed is shorter, which considerably increases the OPEX (2.5 points).…”
Section: Biogasapp_edss Evaluationmentioning
confidence: 99%
“…Physical absorption, currently commercial for siloxane elimination, accomplishes moderate elimination efficiencies and is usually combined with other treatments such as refrigeration [22]. Non regenerative adsorption onto AC is the most widely used to reduce siloxane concentration [23], since it is low energy-consuming and highly effective [24]. Biotrickling filters and membrane separation systems are emerging techniques, although currently under research [25].…”
Section: Introductionmentioning
confidence: 99%